PSYCHOLOGICAL CONDITIONS THAT OCCUR IN TRAFFICKED WOMEN - Butayeva Tamara Alibayevna (American Journals Publishing, 2025)
This article will analyze briefs on psychological tactics used by individuals engaged in trafficking in women affected by trafficking, the problems faced by women affected, and their social, psychological state. The focus is on sexual exploitation and the forced labor of women and other forms of exploitation. Recommendations have also been made on how to approach victims psychologically.